Dynamic Response Analysis of Debris Flow Impacting Bridge Piers Based on the SPH-FEM Coupling Method - Li, Nian; Cao, Chen; Wang, Fei; Jin, Tie (Journal of Research in Science and Engineering, 2026)
Debris flows pose a serious threat to railway bridge piers in mountainous areas due to their high density, strong impact force, and long-duration dynamic loading. To investigate the dynamic response of bridge piers under debris flow impacts, this study adopts a coupled Smoothed Particle Hydrodynamics–Finite Element Method (SPH–FEM). The SPH method models the large deformation and solid–liquid two-phase behavior of debris flow, while FEM simulates the structural response of bridge piers. Refined mesh modeling and elastoplastic constitutive models are applied to capture fluid–structure interaction. Simulations are conducted for 20-year and 50-year return period scenarios, focusing on impact force evolution and energy transfer. Results show that the impact process consists of three stages: initial contact, peak impact, and decay–accumulation. Bridge piers experience both instantaneous peak loads and sustained residual loads, with energy dissipation closely related to structural plastic deformation.